Strategies for Teaching Literacy and Numeracy through The Kampus Mengajar Batch 3 Program at SD Negeri 094164 Partimbalan - Sintia Damanik; Ernawati Tampubolon; Rince Rince; Asima Rohana Sinaga; Fatmawati Sihotang (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2022)
As a result of this pandemic, learning activities must be carried out in a limited manner, which in SD Negeri 094164 Partimbalan school, by using two sessions in 1 day of the teaching and learning process. This limited learning is certainly very ineffective because students' learning time is reduced, therefore the Ministry of Education and Culture launched a program called Kampus Merdeka Mengajar which provides opportunities for the younger generation to assist learning activities in schools. This activity is carried out to assist teaching and learning activities, namely specifically literacy and numeracy, technology adaptation and assisting school administration. The learning method used in learning at SDN 094164 is offline which still applies health protocols. In the end, the activities of the Kampus Mengajar program provide a lot of benefits for schools, teachers and students with some of the knowledge and experience provided.